Gambaran Stres Mahasiswa Tingkat Akhir dalam Penyusunan Skripsi di FKM Universitas Nusa Cendana Kupang - Mariella Damaris Dida; Afrona E. L. Takaeb; PetrusPetrus Romeo (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Stress is an unpleasant or uncomfortable situation experienced by individuals that can interfere with thoughts, emotions, actions or behaviors in daily life. The purpose of this study is to find out the description of the stress of final year students in the preparation of a thesis at the Faculty of Public Health, Nusa Cendana University, Kupang. The population in this study is 118 students of the class of 2018 and the number of samples is 118 people. This type of research is a descriptive research using a sampling technique in the form of total sampling. The instrument used was the DASS-42 questionnaire. Based on the results of the study, it was obtained that the characteristics of the respondents were more female, which was 83.1% and had a residential status at a boarding house, which was 45.8%. In the stress level category, it was found that FKM students of Nusa Cendana University Kupang, especially the class of 2018, were in the mild category, namely 28.8%. For educational institutions, the results of this study are expected to be useful as a source of information, add knowledge about stress and as input or comparison for future researchers regarding the description of stress in final year students at the Faculty of Medicine, Nusa Cendana University, Kupang.